Komparasi Jinayat dengan Hukum Pidana Nasional dalam Penjatuhan Sanksi terhadap Pelaku Tindak Pidana - Isnin, Harum; Cahyani , Indah Fitri (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2021)
Abstract: Islamic law was accepted and developed in Indonesian society long before the arrival of western law by foreign invaders who controlled Indonesia. Most Indonesian Muslim people place Islamic law into the Indonesian legal system, which consists of Western criminal law, customary law, and Islamic legal systems. This article analyses the comparison between Islamic criminal law and Indonesian criminal law in determining sanctions providing a deterrent effect for criminals. Based on empirical legal research methods, it is found that there are similarities between Islamic criminal law and Indonesian criminal law in the form of purposes and principles. The crime conditions in Islamic criminal law are also the same as the offence contained in the national criminal code. The differences between the two laws are in the sources of law, the sanctions attached to each different offence, and the historical evolution that shape the criminal law. This research intends not to compare which crime is better but to find the ideal of criminal law for its betterment in human life.